Law and discipleship: a Muslim reflection on Sharia in light of Bonhoeffer - Zakariyah, Luqman (2013)
Not always the vicegerent of God on the earth gets the spirit of God correctly when interpreting and implementing the Law of God. This stems from the fact that human beings are fallible. This fallibility must be taken into consideration when one speaks on behave of God. Islamic criminal law intrinsically consists both Right of God and Right of Humans. The former is built on clemency and benevolence when it is committed and before it is reported while the latter is engulfed with contention when it is violated. How could a legitimate Islamic government correctly do justice to God by implementing and interpreting His Law without violating the rights of Humans embedded in the Law calls for reconstructing classical interpretation and contextualizing modern implementation of Shariah?